SCHEMES AND CONSTRUCTION SOLUTION FOR SIMPLIFIED COMBINE HARVESTERS BASED ON MULTIPURPOSE AND ROW-CROP TRACTORS - Andrey D. Chistyakov; Yury I. Yermolyev (Advanced Engineering Research, 2012)
Some construction solutions for the simplified combine harvesters based on the universal (croplands) and row - crop tractors, which provide harvesting with much lower expenses than under combining, are offered. The construction solutions are obtained on the basis of the models predicting the directions for the mechanical equip ment develo pment. The component parts and interaction in the harvesting aggregates are developed on the simulati on models